Genome-wide functional analysis of phosphatases in the pathogenic fungus Cryptococcus neoformans - Jae-Hyung Jin (Nature Communications, 2020)
Phosphatases are key components in cellular signalling networks. Here, the authors present a systematic functional analysis of phosphatases of the fungal pathogen Cryptococcus neoformans, revealing roles in virulence, stress responses, O-mannosylation, retromer function and other processes.